Analisis heuristik, monisme, idealisme, dualisme dan pluralisme: berbagai metode penelitian - darmawan, muamal hamdi (Maliki Interdisciplinary Journal, 2025)
Thisi research aimsi to explorei and analyze five main philosophical approaches in understanding reality, namely heuristics, monism, idealism, dualism, and pluralism. The heuristic approach is used as an analytical method to critically and openly compare and evaluate these four metaphysical schools of thought. Monism is the view that all of reality consists of one fundamental principle or emphasizes the unity of the essence of everything, while idealism asserts that everything that exists is rooted in consciousness or non-material entities, where this form of idealism, particularly in the form of spiritualism, views consciousness or spirit as the main foundation of reality. On the other hand, dualism is divided into two different substances, namely matter and spirit, attempting toi explaini thei complexityi of the world through the acknowledgment of the existence of two entities that cannot be reduced to one another. Lastly, pluralism acknowledges the diversity of fundamental elements in the structure of reality.